Piezo-generator integrating a vertical array of GaN nanowires. (1st July 2016) - Jamond, N; Chrétien, P; Houzé, F; Lu, L; Largeau, L; Maugain, O; Travers, L; Harmand, J C; Glas, F; Lefeuvre, E; Tchernycheva, M; Gogneau, N
Abstract: We demonstrate the first piezo-generator integrating a vertical array of GaN nanowires (NWs). We perform a systematic multi-scale analysis, going from single wire properties to macroscopic device fabrication and characterization, which allows us to establish for GaN NWs the relationship between the material properties and the piezo-generation, and to propose an efficient piezo-generator design. The piezo-conversion of individual MBE-grown p-doped GaN NWs in a dense array is assessed by atomic force microscopy (AFM) equipped with a Resiscope module yielding an average output voltage of 228 ± 120 mV and a maximum value of 350 mV generated per NW. In the case of p-doped GaN NWs, the piezo-generation is achieved when a positive piezo-potential is created inside the nanostructures, i.e. when the NWs are submitted to compressive deformation. The understanding of the piezo-generation mechanism in our GaN NWs, gained from AFM analyses, is applied to design a piezo-generator operated under compressive strain. The device consists of NW arrays of several square millimeters in size embedded into spin-on glass with a Schottky contact for rectification and collection of piezo-generated carriers. The generator delivers a maximum power density of ∼12.7 mW cm −3 . This value sets the new state of the art for piezo-generators based on GaN NWs and more generally on nitride NWs, and offers promising prospects for the use of GaN NWs as high-efficiency ultra-compact energy harvesters.